Sulforaphane Inhibits Lipopolysaccharide-Induced Inflammation, Cytotoxicity, Oxidative Stress, and miR-155 Expression and Switches to Mox Phenotype through Activating Extracellular Signal-Regulated Kinase 1/2–Nuclear Factor Erythroid 2-Related Factor 2/Antioxidant Response Element Pathway in Murine Microglial Cells - Eren, Erden; Tufekci, Kemal Ugur; Isci, Kamer Burak; Tastan, Bora; Genc, Kursad; Genc, Sermin (Frontiers in Immunology, 2018)
Sulforaphane (SFN) is a natural product with cytoprotective, anti-inflammatory, and antioxidant effects. In this study, we evaluated the mechanisms of its effects on lipopolysaccharide (LPS)-induced cell death, inflammation, oxidative stress, and polarization in murine microglia. We found that SFN protects N9 microglial cells upon LPS-induced cell death and suppresses LPS-induced levels of secreted pro-inflammatory cytokines, tumor necrosis factor-alpha, interleukin-1 beta, and interleukin-6. SFN is also a potent inducer of redox sensitive transcription factor, nuclear factor erythroid 2-related factor 2 (Nrf2), which is responsible for the transcription of antioxidant, cytoprotective, and anti-inflammatory genes. SFN induced translocation of Nrf2 to the nucleus via extracellular signal-regulated kinase 1/2 (ERK1/2) pathway activation. siRNA-mediated knockdown study showed that the effects of SFN on LPS-induced reactive oxygen species, reactive nitrogen species, and pro-inflammatory cytokine production and cell death are partly Nrf2 dependent. Mox phenotype is a novel microglial phenotype that has roles in oxidative stress responses. Our results suggested that SFN induced the Mox phenotype in murine microglia through Nrf2 pathway. SFN also alleviated LPS-induced expression of inflammatory microRNA, miR-155. Finally, SFN inhibits microglia-mediated neurotoxicity as demonstrated by conditioned medium and co-culture experiments. In conclusion, SFN exerts protective effects on microglia and modulates the microglial activation state.